Sebuah STRATEGI KOMUNIKASI PEMASARAN HYUNDAI PADA BRAND IMAGE KENDARAAN LISTRIK: Analisis Berdasarkan Model Customer-Based Brand Equity (CBBE) di Pasar Otomotif Indonesia - Muhammad Naufal Fadhil Yuwono; Dinda Rakhma Fitriani (Jurnal Spektrum Komunikasi, 2026)
The rapid growth of the electric vehicle (EV) industry has intensified competition among automotive manufacturers, making marketing communication a strategic tool in building a strong brand image. This study examines Hyundai’s marketing communication strategy in building the brand image of its electric vehicles in Indonesia. A qualitative descriptive approach was employed through document analysis and observation of marketing communication materials, including digital campaigns, official publications, promotional activities, and experiential programs. The analysis is guided by Keller’s Customer-Based Brand Equity (CBBE) Model, focusing on brand salience, brand performance, brand imagery, brand judgments, brand feelings, and brand resonance. The findings indicate that Hyundai’s integrated marketing communication strategy effectively strengthens brand awareness and positions the company as an innovative and environmentally responsible EV brand. Consistent messaging emphasizing technological innovation, sustainability, and future mobility significantly shapes positive consumer perceptions. The use of digital platforms combined with experiential marketing activities, such as exhibitions and test drives, enhances consumer engagement, trust, and emotional attachment. Furthermore, Hyundai demonstrates competitive advantages through its clear sustainability positioning, innovation-driven brand narrative, and consistent communication across channels. The study concludes that Hyundai’s marketing communication strategy plays a significant role in building electric vehicle brand image and strengthening brand equity in the Indonesian automotive market. This research contributes to marketing communication studies, particularly in the context of sustainable and innovation-based product branding.